Global perspectives on the role of dialogue in history education
1 online resource (xiv, 223 pages)
Keywords: "Providing the first volume-length exploration of the role that dialogue has played in history education classrooms, this book explores the socio-cultural, psychological, and digital dimensions of dialogic practice to promote research into historical thinking, historical consciousness, and critical thinking in educational settings. Amongst existing literature on rival histories, contested narratives, post-conflict societies, and argumentation in classroom and societies, this book's novel approach is in its analysis of dialogical processes in various international and intercultural educational contexts; chapters compare Israeli and Palestinian textbooks and classroom discussion, explore teacher identities and historical silence in US contexts, and demonstrate research findings into Norwegian approaches to enhancing dialogic practices in history education. Innately tied up with the political motivations and complexities of the geographical context, each case study provides an insight into the nature of dialogue as both shared historical inquiry and cultural practice. Ultimately, the book looks to foster a nuanced and complex understanding of history, prompting consideration of different perspectives and a collective approach to overcoming troubled pasts and trauma. Featuring a truly international set of contributions from established and emerging scholars, this book will appeal to scholars, researchers, and postgraduate students interested in the history of education, education policy and politics, and historiography more broadly"--